Isolation, identification and quantification of flavonoids from the flowers of Staphylea pinnata L. - A. Y. Sokolova; A. M. Poluyanov; A. I. Bardakov; S. S. Sologova; N. V. Bobkova (Разработка и регистрация лекарственных средств)
Introduction. Search for new plant species containing biologically active substances (hereinafter – BAS) is one of the leading tasks of pharmacognosy as a science. The search for flavonoid glycosides in plant raw materials is especially relevant, since they have anti-inflammatory, antioxidant, immunostimulating, as well as weak fungicidal and bacteriostatic action. Staphylea pinnata L. is an endemic plant of the Caucasus, cultivated not only in Georgia, but also in the Russian Federation in the Northern and Northwestern Caucasus. In foreign literature there are studies of antioxidant, antiproliferative and cytotoxic activity of leaf extracts of several species of S. pinnata L., as well as inhibitory activity of COX-1, COX-2 and LTB4 formation. Meanwhile, no serious Russian-language scientific studies on either the chemical composition or pharmacological action of generative organs of S. pinnata were found in the literature. This work is part of a comprehensive phytochemical study of S. pinnata. The aim of the work is to study the qualitative and quantitative composition of flavonoids in the studied object.Aim. To isolate, identify and quantify flavonoids in flowers and buds of Staphylea pinnata L.Materials and methods. Alcohol-water extracts from dried generative organs of the studied plant were used as analyzed solutions. Solutions were analyzed on a spectrophotometer SF-2000 (LLC "OKB Spectr", Russia) after sample preparation with aluminum chloride and on an HPLC Nexera-i LC-2040 (Shimadzu Corporation, Japan) equipped with a column and sample thermostat, degasser and autosampler using an individually selected elution gradient of the mobile phase (0.1 % orthophosphoric acid/acetonitrile solution). The primary data were processed using LabSolutions Single LC software (Shimadzu Corporation, Japan). Compounds from the flavonoid group were identified by retention times. Detection was carried out using a UV detector with an absorption wavelength of 365 ± 2 nm.Result and discussion. Alcohol-water extracts from flowers and buds of S. pinnata L. were obtained. Quantitative evaluation by spectrophotometry for flavonoid content was carried out. A gradient elution mode for HPLC was selected for simultaneous determination of 7 flavonoid glycosides. These chromatographic conditions allowed the identification and quantification of astragaline, cynaroside, cosmosiin, narcissin and rutin in flowers and buds of Staphylea pinnata L. Flavonoid glycosides: raponticin and kaempferol were not detected.Conclusion. Flavonoid glycosides were isolated from the generative organs of S. pinnata L., a technique for quantitative determination of flavonoid glycosides in alcohol-water extracts was developed, astragalin, cynaroside, cosmosiin, narcissin and rutin were detected and quantified.